Perinatal Light Imprinting of Circadian Clocks and Systems (PLICCS): The PLICCS and Cancer Hypothesis - Lewis, Philip; Erren, Thomas C. (Frontiers in Oncology, 2017)
Circadian disruption is associated with sleep, mood, and metabolic disorders, and – according to the International Agency for Research on Cancer [IARC] – even with cancer. Mechanistically, the source of disease may be circadian system instability which likely arises during development. In animal experiments, both low perinatal light:dark ratios and chronic perinatal photoperiod phase shifting yields enduring, detrimental effects on neuroendocrine physiology via circadian system instability. Certainly, accumulating disturbances to neuroendocrine physiology and detrimental downstream effects could predispose to internal cancers. Epidemiologically, either season or latitude of birth, both of which co-determine perinatal photoperiod-zeitgeber strengths, have been utilized independently as proxies for other environmental co-etiologies of cancer. Both have been independently associated with cancer, however the evidence is inconclusive. We hypothesize that time of birth and location of birth, together determining perinatal photoperiod, contribute to cancer development through Perinatal Light Imprinting of Circadian Clocks and Systems (PLICCS).